Various hysterosalpingography findings of female genital tuberculosis: A case series - Nargess Afzali; Firoozeh Ahmadi; Farnaz Akhbari (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Genital tuberculosis is a chorionic disease and mostly occurs by haematogenous spread from extra genital source like lungs, peritoneum, lymph nodes and bones. Transmission through a sexual intercourse is also possible. Since the majority of patients are in reproductive ages, involvement of fallopian tubes and endometrium cause infertility in patients. Cases: Reviewing 4 cases of female genital tuberculosis, which referred to an infertility treatment center with various symptoms, we encountered various appearances on hysterosalpingography (HSG). Conclusion: The genitourinary tract is the most common site of extra pulmonary TB. The primary focus of genital tuberculosis is fallopian tubes, which are almost always affected bilaterally but not symmetrically. Because of common involvement of fallopian tubes and endometrial cavity, disease causes infertility. Diagnosis is not easy because genital tuberculosis has a wide range of clinical and radiological manifestations with slow growing symptoms. Detailed hysterosalpingography finding may be helpful in better diagnosis of the disease. This case series aims to depict the various hystrosalpingographic appearances and pathology produced by tuberculosis and related literatures are reviewed in order to establish a better diagnostic evaluation of genital tuberculosis